Epilepsy beyond seizures: a review of the impact of epilepsy and its comorbidities on health‐related quality of life in dogs. (26th September 2015) - Packer, Rowena M. A.; Volk, Holger A.
Abstract : Epilepsy is one of the most common chronic neurological conditions in the dog, estimated to affect 0.6 to 0.75 per cent of dogs. Owners of dogs with epilepsy have previously indicated that their dog's quality of life (QoL) is of greatest importance to them above seizure frequency; however, much of the research into canine epilepsy to date has focussed on seizure frequency, and how to reduce it via antiepileptic drug treatment. In people, the impact of epilepsy upon QoL has been widely studied, exploring not only its impact on physical health, but also the psychological health and cognitive capabilities of affected individuals. This paper reviews the existing literature on canine epilepsy, identifies potential threats to QoL, and draws parallels from human epilepsy research. We suggest that canine epilepsy poses threats to both quality and quantity of life, with treatment interventions posing a fine balance of potential benefits and harms to the patient. At present, little is known about the neurobehavioural, emotional and cognitive effects of epilepsy upon affected dogs. Further studies are needed to establish the extent to which unknown QoL‐inhibiting comorbidities exist in the dog, in order to avoid their undertreatment, and to objectively quantify the effects of epilepsy on canine QoL.